Design of an expert system for sales in Micro companies diagnosis - Davila Nicanor, L.; Baltazar Escalona, J.C.; Duran Hernandez, J.R. (2023 12th International Conference On Software Process Improvement (CIMPS), 2023)
The study focuses on the economic situation faced by micro, small, and medium-sized enterprises (PYMES, in Mexico) in a post-pandemic context. For this, the results were obtained through national information collected by the "Covid-IE" surveys by the National Institute of Statistics, Geography, and Informatics (INEGI) and publications on this problem of micro, small, and studies to medium-sized companies in Asia. These studies indicate that this category of companies was affected by this health emergency in terms of the decrease in their income, low demand, and lack of inputs and products. In this context, the importance of having technical support that allows systematizing the analysis of scenarios in relation to the risks of certain economic variables that sales will arise is visualized. This will be possible from the perspective of Business Intelligence. In this approach, decision-making can be supported by an expert system to analyze sales scenarios. It will allow establishment criteria in which said economic scenarios are more favorable for the Mexican business sector and other countries in similar situations